WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA APLIKASI BLIBLI.COM DI DKI JAKARTA - Kartio Handoko; Aldina Shiratina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2023)
Objective: The research aims to identity the influence of Brand Image, Celebrity Endorser, andElectronic Word of Mouth towards Consumer’s Buying Decision on Blibli.com. Population in this study are consumers who know and use the Blibli.com application as transaction in DKI Jakarta. The sample used in this study was 200 respondents. The sampling technique using a purposive sampling.Methodology: This research uses a quantitative descriptive approach. Therefore the data analysis used is statistical analysis in the form of SEM-PLS.Finding: H1, H2, and H3 are accepted at a confidence level of 5% and t calculated is greater than t table.Conclusion: The results of this study indicate that brand image has a significant and positive effect on purchasing decisions. Celebrity Endorsers do not have a significant influence on Purchasing Decisions, but celebrity Endorsers should be considered in product sales. In addition, Electronic Word of Mouth has a significant and positive influence on Purchasing Decisions.